If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 2(3n + 2) = -41 Reorder the terms: 3 + 2(2 + 3n) = -41 3 + (2 * 2 + 3n * 2) = -41 3 + (4 + 6n) = -41 Combine like terms: 3 + 4 = 7 7 + 6n = -41 Solving 7 + 6n = -41 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6n = -41 + -7 Combine like terms: 7 + -7 = 0 0 + 6n = -41 + -7 6n = -41 + -7 Combine like terms: -41 + -7 = -48 6n = -48 Divide each side by '6'. n = -8 Simplifying n = -8
| .5x+3=.75x-7.75 | | 12(x)+9=300 | | 41k+11=16 | | 5=7+2x | | 12x+(7-x)2= | | x/3=2/9 | | 2(x+10)=4(x-2) | | -8(4+9x)=3(x-1) | | 25t+30b=750 | | 3x+1=1-3x | | -60+40x=20x | | (t)+2.7=4.5 | | -7(y-2)=-2y+39 | | 6(k-7)-(8+9k)=-4k | | 8n-3(5)= | | x^2+4x=5x | | -2x+21=7x-15 | | 8(2x-4)+5(3x+6)=29 | | (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 |